Human Rights In The Justice System In Indonesia - Ika Novitasari; Asrullah, Asrullah (Kirana Publisher (KNPub), 2022)
To ensure the recognition and protection of human rights, Indonesia has several legal instruments related to human rights. Specifically to try gross human rights violations, Law Number 26 of 2000 concerning Human Rights Courts was enacted. The Human Rights Court is a court within the General Court which is only assigned and authorized to examine and decide cases of gross human rights violations. Investigations into cases of gross human rights violations are within the authority of the National Human Rights Commission. The investigation and prosecution of gross human rights violations is the authority of the Attorney General.